Exploring the stigmatization of fan image in mass media - Tao Yang (SHS Web of Conferences, 2023)
With the continuous progress of network information technology, mass media has become increasingly developed, and Chin’s cultural and entertainment industry has also shown a more diverse scene. At the same time, the development of the cultural and entertainment industry has brought about the development of fan culture. The existing fan base in China is constantly increasing, and the current fan stigmatization is becoming increasingly serious. This article explores the current fan stigmatization in mass media and the reasons behind it. By analyzing the factors such as rapid information diffusion of mass media, group aggression of fan groups, irrational behavior of minority fan groups, and highly binding relationship between fans and idols, the root cause of fan stigma is revealed. On this basis, this article proposes ways to eliminate stigmatization, such as strengthening the supervision of online public opinion, guiding fan groups, promoting positive culture, and strengthening constraints on celebrity capital. By implementing these measures, the stigmatization of fans can be effectively reduced, fostering the growth of a wholesome star fandom and contributing to establishing a virtuous fan community and a more civilized society.